KEMAMPUAN BERPIKIR KRITIS DALAM MENYELESAIKAN SOAL HIGH ORDER THINKING SKILLS (HOTS) PADA MATERI BILANGAN - Yuni Ekawati; SITI NURIYATIN; Nurina Ayuningtyas (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
Critical Thinking is an activity that requires detailed thinking to solve problems and make decisions with the aim of being the competence of daily activities and the future. Learning that is a accordance with critical thinking is high level mathematic leraning High Order Thinking Skills (HOTS) namely the High Order Thinking process in solving mathematic problems that includes the process of analyze and evaluate. The study aims to determine students critical skills in solving High Order Thinking Skills (HOTS) questions. The method used is descriptive qualitative using descriptive methods to solve problems based on the data at the time of the study with a population of class X SMA N 1 KASIMAN school year 2019/2020, a sample of three students taken from the science department. From the research results, one can meet the critical thinking indikator focus, reason, inference, situation, clarity and overiew, while student two meets the critical thinking focus, reason and situation, and the student three also meets the critical thinking indicator focus and reason .